2015
DOI: 10.1128/genomea.01373-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Novosphingobium sp. Strain MBES04, Isolated from Sunken Wood from Suruga Bay, Japan

Abstract: This report describes the draft genome sequence of Novosphingobium sp. strain MBES04, isolated from sunken wood from Suruga Bay, Japan, which is capable of degrading a wide range of lignin-related aromatic monomers. The draft genome sequence contains 5,361,448 bp, with a G+C content of 65.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…strain SYK-6 20 , GGGE metabolism mediated by SDRs and GSTs produces the intermediates MPHPV, GHP, and guaiacol, which were also produced from GGGE by strain MBES04. Among the 58 genes in the strain MBES04 genome 28 that showed similarity to reported SDRs of Sphingomonadaceae family members and encoded short-chain alcohol dehydrogenases, 6 candidate genes were selected based on similarities to the 4 SDR genes reported to function as Cα-dehydrogenases (accession numbers: NC_015976/Gene ID; BAK65539, BAK68041, BAK68265, and BAK68263) in strain SYK-6 20 21 and expressed as His-tagged proteins in E. coli ( Table S2 ). The recombinant SDRs were purified and assessed for their ability to dehydrogenate the Cα position of GGGE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…strain SYK-6 20 , GGGE metabolism mediated by SDRs and GSTs produces the intermediates MPHPV, GHP, and guaiacol, which were also produced from GGGE by strain MBES04. Among the 58 genes in the strain MBES04 genome 28 that showed similarity to reported SDRs of Sphingomonadaceae family members and encoded short-chain alcohol dehydrogenases, 6 candidate genes were selected based on similarities to the 4 SDR genes reported to function as Cα-dehydrogenases (accession numbers: NC_015976/Gene ID; BAK65539, BAK68041, BAK68265, and BAK68263) in strain SYK-6 20 21 and expressed as His-tagged proteins in E. coli ( Table S2 ). The recombinant SDRs were purified and assessed for their ability to dehydrogenate the Cα position of GGGE.…”
Section: Resultsmentioning
confidence: 99%
“…The whole-genome shotgun sequence of strain MBES04 was previously determined by our group 28 . A total of 124 contigs were deposited at DDBJ/EMBL/GenBank under the accession numbers BBNP01000001 to BBNP01000124.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that a combination of six enzymes produced using genes from a marine Novosphingobium strain, which was isolated from sunken wood in Suruga Bay, Japan, entirely converted a racemic lignin‐ model dimer into its respective monomer in three steps (Scheme ) . Two short‐chain dehydrogenase/reductases (SDRs; EC 1.1.1.–) (SDR3, SDR5) and two glutathione S ‐transferases (GSTs; EC 2.5.1.18) with β‐etherase activity (GST4, GST5) that catalyze the first and second steps, respectively, were strictly stereospecific.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Currently,a romatic monomer production from lignin preparationsu sing enzymesh as not been successful and has resulted in only at race amounto f aromatics, such as ferulic acid andv anillinf rom alkali lignin. [23] Recently,w ereported that ac ombination of six enzymes produced using genes fromamarine Novosphingobium strain, which was isolatedf rom sunken woodi nS uruga Bay,J apan, [24] entirely converted ar acemic lignin-model dimer into its respectivem onomer in three steps (Scheme1). [17,25] Twos hortchain dehydrogenase/reductases (SDRs;E C1 .1.1.-) (SDR3, SDR5) and two glutathione S-transferases (GSTs; EC 2.5.1.18) with b-etherasea ctivity (GST4, GST5) that catalyzet he first and second steps, respectively,w ere strictlys tereospecific.…”
Section: Introductionmentioning
confidence: 99%